Nordic Pole Walking for Individuals With Cancer: A Feasibility Randomized Controlled Trial Assessing Physical Function and Health-Related Quality of Life. Issue 2 (April 2020) - Cunningham, Elise; Weaver, Robert R.; Lemonde, Manon; Dogra, Shilpa; Nonoyama, Mika L.
Abstract : Background: Individuals with a diagnosis of cancer tend to be inactive and have symptoms that impact quality of life. An individualized, community-based Nordic pole walking (NPW) program may help. Methods: Primary Objective : To assess feasibility using the Thabane framework of a randomized controlled trial (RCT). Secondary Objective : To determine the effects of NPW on physical function (Six-Minute Walk Test [6MWT], 30-second [30-s] chair stand test, Unsupported Upper-Limb Exercise Test, handgrip strength, physical activity [PA]), and health-related quality of life (HRQOL, 36-item Short-Form Health Survey [SF-36]). The Study Design : An 8-week multicentered block RCT (no blinding) comparing a community-based NPW program (vs usual daily routine) for adults with non-small cell lung, prostate, colorectal, and endometrial cancer. Results: Eight individuals were enrolled in the study with n = 4 per group (1 dropout in the NPW arm; = 67 ± 6 years). The study was deemed "feasible with modifications." NPW significantly improved (statistically and clinically) the 30-s chair stand test when compared with baseline. There was improved 6MWT, PA levels, and SF-36 when compared with the control group (not statistically significant). No adverse events occurred. Discussion, Limitations, and Conclusions: NPW was feasible for individuals with cancer and may improve physical function, PA, and HRQOL. Larger samples are required to determine efficacy and/or program effectiveness. Future programs should include collaboration with hospital cancer centers and support groups, promotion of participant and community engagement with NPW, and consideration of the population's unique characteristics. NPW programs should include individualized exercise prescriptions, behavior change techniques, social aspects, HRQOL assessments, and device-measured PA.